Financial and symbolic incentives promote "green" charging choices - Kacperski, Celina; Kutzner, Florian (Transportation research. Part F, Traffic psychology and behaviour, 2020)
Electromobility can contribute to a reduction in greenhouse gas emissions if usage behavior is aligned with the increasing availability of renewable energy. To achieve this, smart navigation systems can be used to inform drivers of optimal charging times and locations. Yet, required flexibility may impart time penalties. We investigate the impact of financial and symbolic incentive schemes to counteract these additional costs. In a laboratory experiment with real-life time costs, we find that monetary and symbolic incentives are both effective in changing behavior towards ‘greener’ charging choices, while we find no significant statistical difference between them.
Gesehen am 21.04.2020